2009
DOI: 10.1016/j.breast.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The prone technique for breast irradiation – is it ready for clinical trials?

Abstract: This study shows that prone breast irradiation for patients with large or pendulous breasts can be readily developed in radiotherapy treatment centers and could be tested for efficacy in a large, multi-centre randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…21/25 (84%) patients satisfactorily completed 173/192 (90%) planned prone RT fractions. This is fewer than reported in previous feasibility studies of the prone position (3)(4)(5)(6)(7)(8)(9). This may have been because our protocol specified tolerance criteria for set-up errors beyond which women were required to complete treatment in a supine position.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…21/25 (84%) patients satisfactorily completed 173/192 (90%) planned prone RT fractions. This is fewer than reported in previous feasibility studies of the prone position (3)(4)(5)(6)(7)(8)(9). This may have been because our protocol specified tolerance criteria for set-up errors beyond which women were required to complete treatment in a supine position.…”
Section: Discussionmentioning
confidence: 77%
“…Data suggest that prone treatment is feasible (3)(4)(5)(6)(7)(8)(9), but results of studies using electronic-portal imaging (EPI) to investigate inter-fractional variations in breast-tissue position during prone treatment are conflicting (8,9). Morrow et al (9) reported individual-patient systematic errors of 0.1-16.5mm with a pooled random error of 5.4mm and calculated, using the van Herk formula (10), a CTV-PTV margin of 20mm for prone PBI.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to evaluate the feasibility of using 64‐slice spiral CTA to help delineate the substructures of the heart in patients that underwent left breast‐conserving surgery, and to compare the dosimetric difference between IMRT plans in the prone and supine positions. In most studies, the LAD was contoured based on the anatomy instead of based on an image of the virtual structure, (19,16) which may have caused increased intra‐observer bias. The LAD can also be observed during PET scanning.…”
Section: Discussionmentioning
confidence: 99%
“…By pulling the breast away from the chest wall, this position can reduce the dose to the lung, heart, and contralateral breast. The breast becomes longer and narrower, which provides better dose distribution and uniformity (9,11,15‐18) …”
Section: Introductionmentioning
confidence: 99%
“…The patient's arm is usually extended overhead to expose the axilla during EBRT. Positioning the patient in a supine position is the common method for treatment, but the current trend is prone position delivery [5][6][7]. Popular immobilization devices include thermoplastics, the Kuske breast applicator (Fig.…”
Section: Background and Clinical Significancementioning
confidence: 99%